Interpreting high levels of unfolded Von Willebrand Factor in patients with the antiphospholipid syndrome - de Laat-Kremers, Romy; Huang, Shengshi; ten Cate, Hugo; Ninivaggi, Marisa; de Laat, Bas; Devreese, Katrien (Frontiers in Immunology, 2024)
IntroductionUnfolded Von Willebrand Factor (VWF) is increased in thrombotic pathologies such as myocardial infarction. Unfolded VWF mediates the binding of platelets without the need for collagen. β2-glycoprotein I (β2-GPI) is a natural inhibitor of the platelet-VWF interaction. The antiphospholipid syndrome (APS) is associated with thrombosis, with an important pathophysiological role of auto-antibodies directed against β2-GPI.Methods(Unfolded) VWF levels were studied in normal controls (n=93), APS patients (n=64), non-APS thrombosis patients (n=39) and non-APS auto-immune disease (AID) patients (n=49.ResultsUnfolded VWF levels were respectively, 53%, 50% and 36% higher in APS patients, non-APS thrombosis patients and AID patients, compared to normal controls (p<0.0001). Unfolded VWF levels above the 90th percentile in normal controls were associated with an odds of APS (OR: 8.51; CI:3.26 - 22.2; p<0.001), compared to ORs of non-APS thrombosis (OR:5.87; CI:2.07 - 16.7, p=0.001) and AID (OR:3.71; CI:1.40 – 9.87; p=0.009). DiscussionWe found that APS patients have high levels of unfolded VWF in their circulation. In APS, auto-antibodies against-β2-GPI may interfere with the β2-GPI-mediated inhibition of VWF-platelet interaction. Therefore, the higher unfolded VWF levels in APS could in part explain the association of APS and thrombotic complications.